PENGARUH WORK-LIFE BALANCE DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KOMITMEN ORGANISASI : PERAN KEPUASAN KERJA - Winda Rizky Anggraeni; Hengky Widhiandono; Wida Purwidianti; Purnadi (Universitas Sarjanawiyata Tamansiswa, 2026)
This study examines the influence of work-life balance and transformational leadership on organizational commitment with job satisfaction as a mediating variable. This quantitative study collected data using a questionnaire. The study population was all 244 employees of Ananda Purwokerto General Hospital, with a focus on 150 permanent employees, and a sample of 109 permanent employees was obtained through a purposive sampling technique. The data analysis technique used Structural Equation Modeling based on Partial Least Square (SEM-PLS) which was used to test the outer and inner models in measuring validity, reliability, and hypotheses. The results showed that work-life balance had a positive effect on organizational commitment, while transformational leadership had no effect on organizational commitment, work-life balance and transformational leadership had a positive effect on job satisfaction, job satisfaction had a positive effect on organizational commitment, in addition, job satisfaction had a positive effect in mediating the influence of work-life balance on organizational commitment. Job satisfaction had a positive effect in mediating the influence of transformational leadership on organizational commitment.